Gadolinium Deposition in Brain: Current Scientific Evidence and Future Perspectives - Guo, Bang J.; Yang, Zhen L.; Zhang, Long J. (Frontiers in Molecular Neuroscience, 2018)
In the past 4 years, a number of publications described a dose-dependent deposition of gadolinium in the brain both in adults and children, seen as high signal intensities in the dentate nucleus and globus pallidus on unenhanced T1-weighted images. Postmortem human or animal studies have confirmed gadolinium deposition in these areas of T1-hyperintensity, raising new concerns regarding the safety of gadolinium-based contrast agents (GBCAs). Residual gadolinium is retained not only in brain regions, but also in extracranial tissues such as skin, bone and liver. This review summarizes the evidence on gadolinium deposition in the human and animal bodies, evaluates the effects of different types of GBCAs on the gadolinium deposition, introduces the possible entrance or clearance mechanism of the gadolinium and potential side effects that may be related to the gadolinium deposition on human or animals, and puts forward some suggestions for further researches.